Privatization of public enterprises in Nigeria : issues and conditions for success in the second round - Obadan, Michael I. (Ibadan : National Centre for Economic Management and Administration, 2000)
While supporting privatization, the book stresses the need for privatization to be implemented on a pragmatic, enterprise-by-enterprise basis rather than be propelled by ideological considerations.
Includes bibliographical references (p. 98-100).
oif 26/07/16
Loans
Keywords: Privatization; Government business enterprises